Pd/mannose promoted tandem cross coupling-nitro reduction: expedient synthesis of aminobiphenyls and aminostilbenes1. Issue 40 (7th May 2015) - Rohilla, Sandeep; Pant, Pradeep; Jain, Nidhi
<x xml:space="preserve">Abstract</x> d-Mannose as a ligand for Pd catalyzed cross-coupling, and as a hydrogen source for nitro reduction in a modular one-pot cross coupling-nitro reduction sequence.